2005
DOI: 10.1002/chem.200400988
|View full text |Cite
|
Sign up to set email alerts
|

An OsII–Bisbipyridine–4‐Picolinic Acid Complex Mediates the Biocatalytic Growth of Au Nanoparticles: Optical Detection of Glucose and Acetylcholine Esterase Inhibition

Abstract: The complex Os(II)-bisbipyridine-4-picolinic acid, [Os(bpy)(2)PyCO(2)H](2+) (1), mediates the biocatalyzed growth of Au nanoparticles, Au NPs, and enables the spectroscopic assay of biocatalyzed transformations and enzyme inhibition by following the Au NP plasmon absorbance. In one system, [Os(bpy)(2)PyCO(2)H](2+) mediates the biocatalyzed oxidation of glucose and the growth of Au NPs in the presence of glucose oxidase, GOx, AuCl(4) (-), citrate and Au NP seeds. The mechanism of the Au NPs growth involves the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…This system was used to follow the inhibition of AChE through blocking the enlargement of the Au NPs. [27] …”
Section: Enzyme-stimulated Synthesis Of Metal Nanoparticlesmentioning
confidence: 97%
See 1 more Smart Citation
“…This system was used to follow the inhibition of AChE through blocking the enlargement of the Au NPs. [27] …”
Section: Enzyme-stimulated Synthesis Of Metal Nanoparticlesmentioning
confidence: 97%
“…5A). [27] It was reported that in a mixture consisting of GOx, glucose, the electron-transfer mediator [Os(bpy) 2 -…”
Section: Enzyme-stimulated Synthesis Of Metal Nanoparticlesmentioning
confidence: 99%
“…[16] The study of the fluorescence properties of this complex showed a difference in the emission spectra of the reduced and oxidised forms. This phenomenon has allowed us to use this complex as a novel fluorescent probe for the detection of any biomolecule able to oxidise or reduce the Os complex.…”
Section: Introductionmentioning
confidence: 99%
“…The electron transfer turnover rate was also exceptionally high (around 11 800 s − 1 ). Some other enzymes, such as alcohol dehydrogenase (NAD(P) + -dependent enzyme) [19,20] , acetylcholinesterase [21] , and tyrosinase [22] , have been successfully applied to the enzyme/nanoparticle hybrid system.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%